Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Hasil Belajar Matematika dan Kepercayaan Diri Siswa di Kelas IX SMPN 4 Sungai Limau Tahun Pelajaran 2023/2024 - Amanda, Nenda Relia; Risnawita, Risnawita; Aniswita, Aniswita; Medika, Gema Hista (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study was motivated by the low mathematics learning outcomes and self-confidence of students due to their lack of confidence in solving practice questions given by teachers. This research aims to determine the influence of the two stay two stray type cooperative learning model on mathematics learning outcomes and student self-confidence in class IX of SMPN 4 Sungai Limau. This type of research is pre-experimental with The Static Group Comparison Design. The sample was selected by random sampling. Research instruments include lesson plans, student worksheets, learning outcomes tests, and self-confidence questionnaires. Data analysis techniques use normality tests, homogeneity tests and hypothesis tests. Based on analysis of self-confidence questionnaire data using the t test at =0,05 the value of t_count> t_table is 3.7661>1.684 and the average mathematics learning result for the experimental class is 84.33 and the control class is 64.62. Analysis of the final test using the t test at a real level of =0,05 obtained the value of t_count> t_table, namely 4.073> 1.684 so that H_0 is rejected and H_1 is accepted. It can be concluded that there is a significant influence of using the two stay two stray type cooperative learning model on mathematics learning outcomes and student self-confidence in class IX of SMPN 4 Sungai Limau for the 2023/2024 academic year.